Research on Hollow Inclusion Strain Sensors with Temperature Compensation Employed for In-situ Stress Monitor Network - Qifeng Guo; Fenhua Ren; Haoran Guo; Liang Zhao; Zhenxiong Yan (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The hollow inclusion strain sensors employed for in-situ stress monitor use strain gages to detect strain changes of the rock, and the detected strain changes are transmitted to resistance changes in a Whetstone bridge, then the output voltage values of the bridge are finally used for in-situ stress calculation. In order to correct the temperature influence on the strain gages, thermistors are used to record the temperature changes during the monitor and achieve the temperature compensation. A monitor network containing 9 hollow inclusion strain sensors with temperature compensation were built to measure the in-situ stress in an undersea mine, and the measuring results discover the distribution law of 3D in-situ stress state in the mine which can be used to optimize the mining design. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.2948